2009
DOI: 10.3399/bjgp09x420590
|View full text |Cite
|
Sign up to set email alerts
|

Open Access Tubal aSsessment for the initial management of infertility in general practice (the OATS trial): a pragmatic cluster randomised controlled trial

Abstract: BackgroundGPs investigate approximately half of all infertile couples with semen analysis and endocrine blood tests. For assessment of tubal status, hysterosalpingography (HSG) is recommended as a first-line investigation for women not known to have comorbidities. AimTo test whether providing GPs with open access to HSG results in infertile couples progressing to a diagnosis and management plan sooner than with usual management. Design of studyA pragmatic cluster randomised controlled trial. SettingSeventy-one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Other expressions were also used, such as 'routine care', 15,29,35,63 'usual practice', 41 'normal care', 34 'standard care', 49,78 'care as usual', 55 'usual policy', 60 'usual service', 76 and 'usual management'. 84 Other authors did not use a specific expression.…”
Section: Resultsmentioning
confidence: 99%
“…Other expressions were also used, such as 'routine care', 15,29,35,63 'usual practice', 41 'normal care', 34 'standard care', 49,78 'care as usual', 55 'usual policy', 60 'usual service', 76 and 'usual management'. 84 Other authors did not use a specific expression.…”
Section: Resultsmentioning
confidence: 99%
“…Both the pilot survey and the cluster-randomized controlled trial demonstrated a shorter time for couples to reach a diagnosis and management plan for those that had open access HSG performed (Wilkes et al 2006;Wilkes et al 2009a). This was reflected in the opinion of the interviewees.…”
Section: Contextual Integrationmentioning
confidence: 99%
“…In this paper, the results of four studies evaluating open access HSG in the initial management of infertility in general practice were mapped to the NPM constructs (Wilkes, 2007). A brief outline of each study is presented, and the studies themselves are described elsewhere (Wilkes et al, 2006;2007;2009a;2009b Practices allocated to the intervention group had access to HSG for those infertile women who fulfilled pre-defined eligibility criteria. The primary outcome measure was the interval between presentation to the GP and the couple receiving a diagnosis and management plan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The OATS trial, reported in this issue of the BJGP, evaluates hysterosalpingography for the investigation of primary infertility. 5,6 Previous research suggests that the principle benefit for patients of direct access to diagnostic services is reduced waiting time from presentation to testing and hence treatment. Both the DAMASK and OATS trials echo these findings in showing markedly shorter waiting times for those patients whose GPs used direct access.…”
Section: Direct Access To Diagnostic Servicesmentioning
confidence: 99%